Laboratory tests with model based on π circuits considering the introduction of branches composing by RL parallel elements - Pereira, Thaina Guimaraes [UNESP]; Cioquetta Moreira, Aghatta [UNESP]; Colozzo Grilo, Caio Vinicius [UNESP]; Seriramis Menzinger, Juliana [UNESP]; Ferreira, Andre Alves [UNESP]; Jose Do Prado, Afonso [UNESP]; Scheuer, Rene (Institute of Electrical and Electronics Engineers (IEEE), 2019)
For simple transmission line models, it can be applied π circuit cascades. This type of circuits was applied for composing a physical model that has been applied for simulating of propagation of simple electromagnetic transient phenomena. Initiating this physical model, the longitudinal part of one π circuit were obtained and analyzed. This longitudinal part is composed by one inductor in series with four blocks of components. Each block of components is composed by one resistor and one inductor in parallel. From 10 Hz to 1 MHz and considering the mentioned longitudinal part of the circuit powered by sinusoidal voltages, the voltage, the current and the FFT (Fast Fourier Transformation) curves are obtained and analyzed. It is also obtained the time delay between voltage and current waves for each considered frequency value. Subsequently, the transversal section of the π circuit was added to the longitudinal part. This transversal section is composed by resistors and capacitors. So, the transfer function of a complete π circuit unit was obtained and analyzed. Based on the obtained data, it was possible to construct graphs of the resistance, inductance, transfer function and delay angles between voltages and currents by frequency of the π circuit unit. After the analysis of one π circuit, one more unit was added composing a reduced circuit in cascade. The main idea is to obtain a cascade with several units of π circuits for a simple model of transmission lines.
Keywords: Eigenvalues and eigenfuctions; Linear systems; Power system transients; State space methods; Transmission line modelling